(3oZQQ GdMce hoOQQ Gdcdes - (3CHhGdaJM fGUM GdOjf YHO GdhGMO Hf eMeO Hf YHO GdhGMO GdJejej GdBeOjs ((3TajY Hf MGLj CbGNGf s)
(3ChdgG (B:s
(3hHYO, aEf GdPj MOGfj Ydi JNUjU ahGFO gPG GdcJGH hJYdjbgG, hLeY cdeg hJfejbgG s
(3BNQgG (B:s
(3jbHM HGdQLd Cf jbUQ Yedg Yf Ydeg, hjYLR aYdg Yf bhdg ocJHJ gPg GdfSNI s
(3HChd GdfSNI hBNQgG BKGQ JbWjYs
(3hHgG fXGe GdJYbjHIs
(3ef cdGe Ydj Hf CHj WGdH QVj Gddg Yfgs
(3GdeJhai (B40 (3g`` s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdCOHs